The simian foamy virus type 1 transcriptional transactivator (Tas) binds and activates an enhancer element in the gag gene. - Campbell, M (1996)
Simian and human foamy viruses (SFV and HFV) encode a transcriptional transactivator, Tas, which governs the levels of viral transcripts initiated by both the promoter in the long terminal repeat (LTR) and the internal promoter (IP) located within the env gene of these viruses. Tas-responsive target elements,(TRE) LTR in the LTR and (TRE) IP in the env gene, are located 5' of the TATA box in both viral promoters and function as orientation- and position-independent enhancers. We have identified a strong Tas-responsive element, designated TRE (GP), near the 3' end of the gag gene and preceding the pol gene of SFV-1. In transient-expression assays with plasmids containing reporter genes, a 59-bp DNA fragment containing TRE (GP) (nucleotides 2224 to 2282) functioned as an enhancer element, dependent on Tas, in several cell types and in the context of a heterologous basal promoter. DNase footprinting revealed that the fusion protein glutathione S-transferase-Tas, purified from genetically engineered bacteria, interacts with about 40 hp (nucleotides 2237 to 2279) in the TRE (GP). A low degree of sequence homology was noted between TRE (GP) and TRE (IP). In virus-infected cells, novel transcripts with 5' ends immediately upstream from the reverse transcriptase translation frame (nucleotides 2611 to 5778) were identified. Upstream of the start site for these transcripts is a TATA box (nucleotides 2575 to 2579), which was required for transcription in transient-expression assays. Although a spliced mRNA initiated in the viral LTR is implicated in the synthesis of the HFV Pol polyprotein which encodes protease, reverse transcriptase, and integrase, it is possible that SFV-1 contains a promoter within the pol gene for initiating a reverse transcriptase transcript. Taken together, these studies define a novel Tas-responsive enhancer element, which binds the viral transactivator, and a potential promoter within the pol gene.